High Growth Firms in Northern Ireland : A Strategic Appraisal and Policy Assessment : Final Report for the Department for the Economy, Northern Ireland.: A Strategic Appraisal and Policy Assessment : Final Report for the Department for the Economy, Northern Ireland. (2017) - Brown, Ross; Lee, Neil; Mawson, Suzanne
No abstract available